Pemberdayaan Perempuan Melalui Pelatihan Menjahit di Desa Maju Jaya Kecamatan Pemulutan Kabupaten Ogan Ilir Provinsi Sumatera Selatan - Wahyuli, Yofitri Heny; Nella, Mietha; Sukhaidi, Sukhaidi (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
The Covid-19 pandemic has had the impact of weakening the family economy, many workers have been laid off, and businesses are not running optimally. On the other hand, the group of mothers has free time, the potential to be productive independently by working from home, but they don't have the skills yet. So to overcome this problem the service team carried out sewing training service activities. This service activity aims to empower women, increase women's creativity and independence in Mekar Jaya Village, Pemulutan District, Ogan Ilir Regency. This service method is socialization, training, and sewing assistance which includes pattern making, cutting, and sewing. This service activity is carried out face-to-face or offline while adhering to health protocols. Sewing training is carried out in several stages. First, the participants were trained to make patterns using cardboard and then applied them to the fabric. Second, the participants were taught how to cut cloth properly. Third, participants are trained to sew using the correct technique, so the results are neat. The fabric used is Troso woven fabric, so that participants will be able to utilize local Jepara products. The participants' responses to this service showed that 95% of the material aspects rated it very well, the facilitator aspect 90% rated it very well, and the rest responded well. The results of this dedication show that 85% of the participants succeeded in being skilled in sewing, seen from the success of the participants in starting a sewing service business, and convection from cloth after participating in the service activities.